The Effect Of Block Training On Block Skills In Extracurricular Volleyball Players At Man 02 Kepahiang - Defika, Yoba; Martiani, Martiani; Syaputra , Roni (Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of block training on block skills in extracurricular volleyball players at MAN 02 Kepahiang. This type of research is an experimental study with a sample of 16 students. The results of the study indicate that based on the results of data analysis, description, testing of research results, and discussion, it can be concluded: block training can significantly improve block skills